Examining Manufacturing Companies the Lens of Reliability Models and their Performance (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Manufacturing companies operate in dynamic and competitive environments where reliability contribute as a crucial significant part in ensuring efficiency, cost-effectiveness, and product quality. This research examines manufacturing companies through the lens of reliability models to evaluate their operational performance. With the integration of reliability engineering principles with manufacturing performance metrics, the study explores how predictive maintenance, failure rate analysis, and system reliability modelling affect the productivity and sustainability. Various reliability models, including probabilistic, statistical, and machine learning-based approaches, are analyzed to assess their effectiveness in minimizing downtime and optimizing resource utilization. Case studies and empirical data from manufacturing firms are utilized to present an example the practical application of these models. The findings provide insights into best practices for improving manufacturing reliability, reducing operational risks, and enhancing long-term performance. This study contributes to the field of industrial engineering by offering a comprehensive framework for applying reliability models to manufacturing systems, paving the way for more resilient and efficient production processes.